PENGARUH SALES GROWTH DAN CAPITAL STRUCTURE TERHADAP FINANCIAL PERFOMANCE - Prabasari, Bonita; Amalia, Naini Rizka (Solusi, 2022)
This study aims to examine the effect of sales growth and capital structure on financial performance in manufacturing companies in the customer good sector that are listed on the Indonesia Stock Exchange in 2018-2020. The sample used in this study is manufacturing companies that consist and profit in Indonesia Stock Exchange throught 2018-2020. The method of data collection used is purposive sampling with criteria. The data analysis is using Multiple Regression Analysis. The results show that sales growth does not significantly effect on financial performance. While capital structure gives a negative effect on financial performance.  Keywords: financial performance, sales growth, capital structure